Waste Culture and the Nigerian Economy - Adjeketa Blessing (Glocal Society Journal, 2026)
The common perception in Nigeria is that plastic waste, specifically PET waste, is simply a pollutant. However, a growing number of individuals and businesses are discovering its economic potential through aggregation and recycling. To raise awareness about this untapped value, The Nigerian Bottling Company (NBC), part of the Coca-Cola Hellenic Group, produced a documentary titled The Rise of Nigeria’s Recycling Economy: Turning Waste into Opportunity. This documentary was widely disseminated online and on social media. A content analysis and subjective interpretation of the NBC documentary aims to highlight practical waste management strategies that can be implemented at the local level to drive economic growth and promote sustainability within Nigerian communities. The documentary presents a compelling case for viewing plastic waste not just as an environmental burden, but as a valuable economic resource. Through a blend of factual data, narrative storytelling, expert interviews, and impactful audio-visuals, the documentary illustrates the current state of plastic waste management in the country and the potential for significant economic growth through recycling initiatives. It effectively demonstrates how innovative approaches can convert waste into opportunities, fostering both environmental sustainability and economic prosperity within Nigeria.